HISTORY OF ARABIC LEXICOGRAPHY AND THE IMPORTANCE OF ARABIC LEXICON IN LEARNING ARABIC - dian - malinda (Jurnal Ilmiah Pesantren, 2017)
Lexicon or dictionary has the crucial role for those who are learning foreign language. Those also became the most important appliance in acquiring any languages especially for them who teach and learn Arabic. Somehow these days many students and teachers choose to use transliteration dictionary then using dictionary that is written by Arabic. Herewith, in this text the author took discussion on history of Arabic lexicography and the phase transition in Arabic lexicon. Whithin it the reader will find the variety in Arabic lexicon. By understanding the kind of lexicon would help the learner to explore the essence and aesthetic in Arabic words .